Peroxide-based hybrid and prodrug antimalarials to deliver cysteine protease inhibitors into the parasitic food vacuole - Oliveira, Rudi Micael Santiago de, 1986- (2014)
Tese de doutoramento, Farmácia (Química Farmacêutica e Terapêutica), Universidade de Lisboa, Faculdade de Farmácia, 2014